Evaluación técnico – financiera del rendimiento de los motores de imanes permanente con bombas electrosumergibles de alta eficiencia del campo a ubicado en la Cuenca Llanos Orientales (2016)
This project is aimed at evaluating a new technology that can reduce production costs associated to the lifting of fluids in field wells A, where the deposit does not have enough pressure to bring their fluids to the surface, so they must be installed artificial lift systems, the most widely used is the electric submersible pumping due to high oil viscosity and high water production. Production costs of BES system are associated with the consumption of electricity; in the electrosumergible engine not only has the highest power requirement of the system, is also the team that has higher energy losses within its conventional asynchronous models.